2017
DOI: 10.1002/ange.201704084
|View full text |Cite
|
Sign up to set email alerts
|

Fluoreszenzsonden mit mehreren Bindungsstellen unterscheiden zwischen Cys, Hcy und GSH

Abstract: Thiole wie Cystein (Cys), Homocystein (Hcy) und Glutathion (GSH) spielen für das Redoxgleichgewicht in biologischen Systemen eine entscheidende Rolle. Dieser Kurzaufsatz fasst aktuelle Aspekte aus dem Bereich der reaktiven Thiolsonden für die biomedizinische Forschung und Diagnostik zusammen und betont die verbleibenden Herausforderungen für Chemiker im Bereich der selektiven Sonden und Sensoren. Der Fortschritt bei Sonden mit mehreren Bindungsstellen stellt eine kreative neue Richtung des Feldes dar, die glei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 124 publications
0
6
0
Order By: Relevance
“…[23] Although much success has been attained by utilizing reaction-based activation of fluorophores with over-expressed cancer metabolites such as thiols and H2O2, high-performance selective bioimaging and/or treatment of cancerous cells heavily depends on the coordination of carefully designed substrate-fluorophore couples to the relatively over-expressed and/or mutated enzymes followed by the relevant reaction for releasing of the "active" agent. [24] Our survey of the last decade clearly demonstrated that the community is betting on the success of this approach towards realizing the next generation of imaging/treatment options.…”
Section: Bioimagingmentioning
confidence: 97%
“…[23] Although much success has been attained by utilizing reaction-based activation of fluorophores with over-expressed cancer metabolites such as thiols and H2O2, high-performance selective bioimaging and/or treatment of cancerous cells heavily depends on the coordination of carefully designed substrate-fluorophore couples to the relatively over-expressed and/or mutated enzymes followed by the relevant reaction for releasing of the "active" agent. [24] Our survey of the last decade clearly demonstrated that the community is betting on the success of this approach towards realizing the next generation of imaging/treatment options.…”
Section: Bioimagingmentioning
confidence: 97%
“…In recent years, on the basis of successful developments of a variety of fluorescent probes for biothiols, fluorescent detection of biothiols in biological samples can be easily realized. [7,30,31] However, because the reactivity of three biothiols is very similar, their differential detection using one fluorescent probe is difficult. [28] Therefore, a multi-functional probe that can detect and discriminate biothiols in biological samples is highly desirable.…”
Section: Design Synthesis and Characterization Of [Eu(nbdketo) 3 (Dpbt)]mentioning
confidence: 99%
“…[16][17][18] In recent years, a large number of fluorescent indicators have been developed to distinguish and measure thiols by taking advantage of the strong nucleophilicity of the thiol group. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Despite significant progress achieved to selectively distinguish thiols from other amino acids, most of the methods suffer from the limitation of differentiation of Cys, Hcy, and GSH from each other due to the similar structures and reactivities of these thiols. Consequently, we are intent on designing and synthesizing novel fluorescence sensors that can effectively discriminate Cys, Hcy and GSH.…”
Section: Introductionmentioning
confidence: 99%